Tunes, Tubes and Clouds: Getting Your In-House Talent Out of the House and Online. Part 1: Production. (16th March 2016) - Bates, Daniel
Abstract: In his first of two articles, Daniel Bates explains the process for creating high quality audio and video recordings to capture knowledge or experience in your organisation, either for internal or external consumption. The article arises from a paper delivered at the 2015 BIALL Conference. The second article will consider the online platforms which are available to host and promote such content.